Consumer Investment in Product-Specific Capital: The Monopoly Case - Holmes, Thomas J. (Quarterly Journal of Economics, 1990)
Journal Article Consumer Investment in Product-Specific Capital: The Monopoly Case Get access Thomas J. Holmes Thomas J. Holmes University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 105, Issue 3, August 1990, Pages 789–801, https://doi.org/10.2307/2937899 Published: 01 August 1990